Re-evaluating the strength of pit-latrine faecal sludge from dynamic cone penetrometer test data - Shafiq, Yasmine; Haigh, Stuart; Holm, Rochelle; Parker, Alison (Water Research Commission, 2020)
In 2017, 55% of the global population were without safely managed sanitation services. On-site sanitation solutions, such as pit latrines, provide the majority of sanitation coverage across developing countries. Appropriate technologies are required in order to safely empty these latrines without damage to people or the environment. The design of appropriate emptying technologies can be hampered by a lack of knowledge of the mechanical properties of the waste, such as its strength. This paper will develop a calibration for a dynamic cone penetrometer to give accurate measurements of faecal sludge strength against a standard scale, rendering existing data comparable. It will be shown that the maximum shear strengths of faecal sludge found in practice are substantially greater than those previously reported; some pit latrines contain faecal sludge with strength values of 5–20 kPa at the surface, and exceeding 80 kPa at depth
Keywords: pit latrine; dynamic cone penetrometer; strength measurement; faecal sludge